Determinants of the mortality of Patin fish in Temerloh, Pahang, Malaysia - Ayuob, Mohammad; Mustafa, Hasri; Johari, Jalila (Global Mainstream Journal, 2024)
This study explores the factors influencing Patin fish mortality in Malaysia's expanding aquaculture industry, which is crucial for meeting the rising global demand for fish and seafood. Analysingdata from 135 fish farmers through SPSS Software, it finds significant correlations between mortality rates and variables like fish species, time until sale, and fish quantity per cage. At the same time,factors such as partnership numbers and feeding frequencyhave minimal impact. These results highlight the critical role of water quality management in fish health and production costs. The findings are vital for developing strategies to improve fish farming and water quality control in Malaysia, addressing the need to consider various factors to reduce fish mortality. Despite the significance of certain variables, the low adjusted R-squared value points to other yet unidentified factors affecting fish deaths, suggesting ongoing data collection and model refinement for stakeholders. This research contributes to understanding aquaculture costs and fish health, informing theories such as Interactive Governance Theory, Stress Response Theory, and Disease Ecology Theory and underscoring the importance of comprehensive strategies for sustainable aquaculture practices